Exploring potential sources of childhood trauma: A qualitative study with autistic adults and caregivers. (November 2022) - Kerns, Connor M; Lankenau, Stephen; Shattuck, Paul T; Robins, Diana L; Newschaffer, Craig J; Berkowitz, Steven J
The stressors autistic individuals encounter and experience as traumatic may vary from non-autistics. We conducted a qualitative study to identify potential sources of trauma for autistic individuals and evaluate correspondence with a standard measure. We enrolled autistic adults ( N  = 14) and caregivers ( N = 15) with varied adversities, levels of functioning, and socio-demographics. Participants completed standard measures of autism, traumatic exposures and stress, and qualitative interviews, which were submitted to thematic analysis. A wide range of experiences were described as traumatic. Whereas some reflected traditional traumas (e.g. maltreatment) and forms of social marginalization, others reflected conflicts between autistic characteristics and the environment (e.g. sensory trauma). All adults and caregivers described sources of trauma in interviews not captured by standardized measures. Varied stressful experiences, many not detected by a standardized measure, may have a traumatic effect on autistic individuals. Whereas some reflect commonly recognized trauma sources, others may reflect particular vulnerabilities for autistic individuals. Results have implications for assessing traumatic events and understanding their contribution to mental health inequities in the autistic population. Lay abstract: The stressors autistic individuals encounter and experience as traumatic may vary from those not on the spectrum and typically measured. We conducted in-depth interviews with autistic adults and caregivers of children and adults on the spectrum to identify potential sources of trauma for autistic individuals and evaluate the ability of a standard trauma measure to capture those experiences. Fourteen autistic adults and 15 caregivers with varied backgrounds, clinical profiles, and histories of adversity were interviewed. Participants also completed standard measures of autism, traumatic exposures, and stress. Interviews were analyzed to record both traditional sources of trauma, for comparison with the standard measure, and distinct sources, described as traumatic only in the narratives of participants. Participants described varied experiences as traumatic. Whereas some reflected traditional traumas (e.g. maltreatment) and forms of social marginalization, others reflected conflicts between autistic characteristics and the environment (e.g. sensory trauma). All adults and most caregivers described sources of trauma in interviews not reported on the standard measure. Results have implications for assessing traumatic events in autism and for understanding their contribution to the mental health of this group.